Sino-Africa Relations and Implications for Neo-colonialism: a Case of China’s Involvement in Ghana’s Textiles and Mining Industries and its Implications in Achieving the Sustainable Development Goals in Ghana - Yeboah, Gideon Asante; Acheampong, Kelvin; Ebbey, Prince Henry (Africana Studia, 2023)
China’s progressive assumption as a major actor on the African scene needs critical academic attention and examination. Although there are undoubtedly varied benefits, there are also concerns about whether China’s win-win rhetoric is sincere or just empty propaganda. This paper contributes to the debate by examining the relationship between China and Africa through the lens of neo-colonialism. In this regard, the paper examines China’s involvement in the textiles and mining industries of Ghana as a case study to argue whether the partnership between China and Africa is one that actually promotes development or engenders a new trend of neo-colonialism. Since this research focuses on areas such as partnership (i.e., between Ghana and China) and illegal mining with its effects, it intersects four of the SDGs (clean water and sanitation [SDG 6]; sustainable cities and communities [SDG 11]; life below water [SDG 14]; and partnership for the goals [SDG 17]. Keywords: Neo-colonialism, mining, textiles, sustainable development.